Beginning Kotlin : Build Applications with Better Code, Productivity, and Performance - Hagos, Ted (Apress L. P., 2022)
This book introduces the Kotlin programming skills and techniques necessary for building applications. You'll learn how to migrate your Java programming skills to Kotlin, a Java Virtual Machine (JVM) programming language. The book starts with a quick tour of the Kotlin language and gradually walks you through the language in greater detail over the course of succeeding chapters. You'll learn Kotlin fundamentals like generics, functional programming, type system, debugging, and unit testing. Additionally, with the book's freely downloadable online appendices, you'll discover how to use Kotlin for building Spring Boot applications, data persistence, and microservices. What You Will Learn Learn the Kotlin language, its functions, types, collections, generics, classes, and more Dive into higher-order functions, generics, debugging, and unit testing Apply the fundamentals of Kotlin to Spring Boot Add Hibernate to your Spring Boot application for persistence and data accessibility Take advantage of functional programming available in Kotlin Who This Book Is For Java developers who are new to Kotlin and want to leverage Kotlin, particularly for building Spring Boot apps.